Chip Off the Old Block: Generation, Development, and Ancestral Concepts of Heredity - Poczai, Péter; Santiago-Blay, Jorge A. (Frontiers in Genetics, 2022)
Heredity is such a fundamental concept that it is hard to imagine a world where the connection between parents and offspring are not understood. Three hundred years ago thinking of the phenomenon of heredity bore on a cluster of distinct philosophical questions inherited from antiquity concerning the nature and origin of substances or beings without any biological meaning. We are reminded of this philosophical heritage by the fact that in the eighteenth century the study of reproduction, embryology and development was referred to as “the science of generation”. It is now clear to everyone that reproduction, the biological process by which parents produce offspring, is a fundamental feature of all life on Earth. Whereas heredity, the transmission of traits from parents to offspring via sexual or asexual reproduction, allows differences between individuals to accumulate and evolve through natural selection. In general, genetics is the study of heredity, and in particular, variation of fundamental units responsible for heredity. Ideas underlaying this theory evolved in considerably different and unrelated ways across a number of knowledge domains, including philosophy, reproduction, development, medicine, natural history, and breeding. The fusion of these different domains into a single comprehensive theory in nineteenth century biology was a historically and culturally interdependent process, thus examining genetic prehistory should unravel these entanglements. The major goal of our review is tracing the various threads of thought that gradually converged into our contemporary understanding of heredity.